EVALUATION OF THE PARAMETERS OF CHARQUI MEAT AND JERKED BEEF MARKETED IN SOUTH OF BRAZIL - Coelho, Alexandre Rodrigo; Garcia Coró, Fábio Augusto; Fontana, Herrison Yoshiki Yocida (IJRDO-Journal of Applied Science, 2017)
Charqui and jerked beef, typical foods from certain regions of the Brazil. These products are interesting due to the added value to less noble meat, to meat from older animals and of doubtful sensory quality for fresh consumption. Physicochemical and microbiological analyses were performed on four different trademark of charqui and on three of jerked beef. The physicochemical tests were ascertained by moisture contents, ash, water activity (Aw) and pH. Regarding the microbiological testing, there was the estimated count of total coliforms and thermotolerants (MPN/g) and the enumeration of coagulase positive Staphylococcus. The objective of this study is to evaluate the quality of Charqui and jerked beef marked in the Southern Region of Brazil. The physical-chemical data for the samples analyzed were in accordance with the standards expected in current laws.